Implementasi Digital Marketing melalui Media Sosial terhadap Perkembangan Brand Awareness Toko Konvensional Haris Jaya Motor - Victor Ryan Sanjaya; Vincentius Alexander; Agung Stefanus Kembau (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
Brand awareness is an important element in building competitiveness and expanding the market reach of Toko Haris Jaya Motor, seeing the great potential in digital marketing as a means to strengthen brand image amidst increasingly competitive industry competition. The purpose of this project is to design an effective digital marketing strategy to encourage increased brand awareness of Toko Haris Jaya Motor. The methods used in this project include data collection through in-depth interviews and direct observation of Toko Haris Jaya Motor's marketing activities. The findings from the research are analyzed to produce a digital marketing strategy to increase brand awareness that includes optimization of social media. The strategy also includes the development of creative and relevant content for social media platforms such as Instagram and TikTok, taking into account the characteristics of each channel and the behavior of the target audience. The final results of this project show that the integration between social media designed based on user analysis can have a positive impact on increasing the company's brand awareness.